1999
DOI: 10.1177/004005999903200208
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills for Social Ills

Abstract: Tell me more about it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Paraprofessional supports were not purposely initiated as a preferred model to facilitate quality education, yet they have been maintained and expanded in the absence of a supportive theoretical basis or efficacy data. Only in the late 1990s did a small set of nondatabased literature and corresponding research begin to raise serious questions about the appropriateness of support models that rely heavily on paraprofessionals to provide instruction to students with disabilities (Brown et al, 1999;Freschi, 1999;Giangreco et al, 1997;Marks, Schrader, & Levine, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Paraprofessional supports were not purposely initiated as a preferred model to facilitate quality education, yet they have been maintained and expanded in the absence of a supportive theoretical basis or efficacy data. Only in the late 1990s did a small set of nondatabased literature and corresponding research begin to raise serious questions about the appropriateness of support models that rely heavily on paraprofessionals to provide instruction to students with disabilities (Brown et al, 1999;Freschi, 1999;Giangreco et al, 1997;Marks, Schrader, & Levine, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, when acted upon, this assumption favors more restrictive settings for students with ASDs. It is critical to identify how those practices that benefit students with ASDs, including structure (visual supports, communication supports, and social supports), positive behavior supports, and systematic instruction, can be implemented meaningfully and seamlessly in general education settings (Dunlap, Kern, & Worcester, 2001; Marks & Shrader, 1999; Quill, 1997). It is recommended that those who place students with ASDs in educational settings determine the unique needs of the individual, and match those needs to specific supports and services that will be provided in general education settings.…”
Section: Recommendationsmentioning
confidence: 99%
“…Although the assignment of a paraprofessional is intended to positively impact the student, several studies have shown that the presence of a paraprofessional can actually have detrimental effects on the peer interactions of a student with a disability (Giangreco, Edelman, Luiselli, & MacFarland, 1997;Marks, Schrader, & Levine, 1999;Shulka, Kennedy, & Cushing, 1999). Specifically, Giangreco et al (1997) found that paraprofessional proximity had a profoundly negative impact on peer interactions, which affected relationships with classmates.…”
mentioning
confidence: 99%